Analisis Dialek Bahasa Arab Peranakan di Condet Jakarta Timur - Muhammad Rifat Michel Thalib; Muhammad Sauqi Nur (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research examines the Peranakan Arabic dialect in Condet, East Jakarta, as a representation of cultural acculturation between Hadrami Arab society and local Indonesian culture. This dialect is the result of a unique blend of standard Arabic with elements of Indonesian and Javanese, reflecting a long history of migration and cultural interaction. This research aims to analyze linguistic characteristics, social roles, and challenges faced in maintaining this dialect. The research method used is descriptive-analytical with a qualitative approach. Data was obtained through in-depth interviews with native speakers, participant observation, and literature review. The research results show that this dialect has distinctive characteristics in the form of loan-word vocabulary, phonological changes, and intonation patterns that are influenced by the local language. This dialect not only functions as a means of communication, but also as a symbol of Peranakan Arab identity and solidarity in Condet. However, globalization and shifts in language use among the younger generation pose a threat to the sustainability of this dialect. Therefore, preservation efforts are needed through documentation and cultural education. This research contributes to linguistic studies, especially Arabic dialects in Indonesia, and is the basis for preserving the Peranakan Arab cultural heritage as part of Indonesia's cultural richness.